Religious tourism and life satisfaction: the role of motivation, perceived value and social cohesion - Shang-Pao Yeh; Tai-Ying Chiang; Jia-Hao Zhong; Shih-Shuo Yeh (Journal of Tourism, Heritage & Services Marketing, 2024)
Purpose: This study aimed to explore the relationships between religious tourism motivation (RTM), tourist perceived value (TPV), social cohesion (SC), life satisfaction (LS), and fear induced by COVID-19 (FC). The focus was on understanding how these factors interacted during the Dongshan Welcomes the Buddha parade, particularly in the context of the ongoing pandemic. Dongshan is a small town in Tainan, Taiwan.